Juridic Implications of Government Policy in Law on the Implementation of Higher Education Foundations - A. Zulkarnain (Budapest International Research and Critics University, 2022)
This study focuses on the implications of government policies in legislation on the implementation of higher education. This research method is normative with a concept/theory approach, legislation, and cases. The data used is secondary data in the form of primary and secondary legal materials. The results of the study indicate that government policies in the legislation on foundations and higher education have implications for the establishment of foundations which were previously based on custom and jurisprudence, and were then required to conform to the law on foundations. On the management side, foundation organs consisting of coaches, administrators and supervisors are required to comply with the applicable foundation and higher education laws and regulations. by maximizing the performance of the elements of the foundation's organs and the existing higher education leaders according to their respective duties and functions and responsibilities to realize the social goals of the foundation. Foundation organs are prohibited from holding concurrent positions within the foundation and in the administration of higher education. In the appointment of foundation organs, it is forbidden to be affiliated between the coaches, administrators and supervisors. Supervision of foundations is carried out by internal supervisors appointed by the foundation, and external supervisors from the government, namely from relevant agencies and the community. Deviations in the organization of foundations and higher education institutions may be subject to criminal, civil and administrative sanctions according to the type and level of violation of the organ concerned.